Substitusi Benang Akrilik Sintetik dengan Benang Alami Bambu pada Mesin Rajut IKm Saung Rajut - Salsabila, Fairuz Salma; Syahputri, Marwah Annie; Savira, Aulia Bella; Putri, Sheila Andita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Replacing acrylic knitting threads which are the most used material in Knitting production at Saung Knitting IKM, natural bamboo threads can also be another alternative. This research aims to innovate IKM Saung Knitting materials so that they can produce natural knitting products. The approach method used is a qualitative method. With direct experiments on machines, bamboo yarn has the potential to produce knitwear that resembles acrylic because of its soft and environmentally friendly character.